The Control Techniques drives and controls handbook - Drury, Bill (Institution of Electrical Engineers, 2001)
Annotation This handbook contains technical information for practicing drive and electrical engineers, covering the technology underlying drives, motors, and control units and modern practical applications. There are chapters on industrial motors, power electronics, speed and position feedback devices, drive control, switched-reluctance and stepper-motor drives, and practical drives, and on communication systems, electromagnetic compatibility, and systems design. The book concludes with summaries of the relevant international standards, a list of symbols and formulae, reference tables, and a chart on world industrial electricity supplies. Drury works in the private sector. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Keywords: Electric motors.; Electric controllers.; Electric driving.; elektronické knihy; electronic books